The potential function of soy protein hydrolysate to induce myogenic differentiation of C2C12 cells - Yinglei Chen; Changwu Xiong; Yingzhi Wan; Mengjun Sun; Zhong Zheng; Dayou Liu; Huilin Liao; Yueqing Wang; Yexu Wu (PLoS ONE, 2025)
Muscle satellite cell (MSC) isolation, proliferation, and differentiation are the basis of cultured meat (CM) technology, which emerged as a sustainable and moral substitute for conventional animal agriculture. Notwithstanding the encouraging future of CM, there are still a lot of obstacles to overcome, like the high expense of cell culture media and the need for fetal bovine serum (FBS). The goal of this work is to determine whether plant-based nitrogen source soy protein hydrolysate (SPH) can improve myogenic differentiation and functional development in MSCs cultured for CM by acting as a serum substitute. We concentrated on how Angel Yeast Company’s SPH PU041 affected the C2C12 mouse cell line, a useful model for studying muscle biology and the CM sector. Adding PU041 to cell culture media containing different concentrations of FBS was found to promote C2C12 cell proliferation and elongation, with optimal effects observed at 0.5 g/L. Immunofluorescence and flow cytometry analyses revealed that PU041 up-regulated the protein levels of myosin heavy chain (MyHC) and myogenic differentiation factor 1 (MyoD), key biomarkers in myogenesis. Furthermore, quantitative real-time PCR (qPCR) confirmed the up-regulation of MyHC, MyoD, and myogenin (MyoG) mRNA expression, indicating that PU041 induces myogenic differentiation. The findings suggest that SPH PU041 can potentially be used to reduce the costs associated with CM production as a viable serum substitute, thereby facilitating a more sustainable and ethical approach to food production. However, the precise mechanisms underlying PU041’s effects on myogenic differentiation warrant further investigation.